The Influence Of Personalization, User Experience, And Digital Marketing Strategy On Customer Loyalty With Churn Rate As A Mediating Variable In The E-Commerce Industry - Reni, Agus Tamrin (Jurnal Ilmu Sosial Mamangan, 2025)
This study investigates the influence of personalization, user experience, and digital marketing strategies on customer loyalty in the e-commerce industry, with churn rate acting as a mediating variable. Utilizing a quantitative research approach, data was collected from active e-commerce users through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results reveal that personalization, user experience, and digital marketing strategies significantly impact customer loyalty, both directly and indirectly through churn rate. Personalization creates tailored customer experiences that enhance loyalty, while user experience and targeted digital marketing strategies reduce churn and foster long-term customer retention. The mediation analysis confirms that churn rate plays a pivotal role in strengthening these relationships. These findings highlight the importance of adopting personalization, advanced marketing strategies, and user-friendly platform designs as critical components for improving retention and loyalty in the competitive e-commerce sector.